MODELS FOR INCREASING THE COMPETITIVENESS OF THE AGRICULTURAL NETWORK IN THE AGROCLUSTER SYSTEM AND STRATEGIES FOR THEIR APPLICATION (Marketing Journal, 2025)
510 This article analyzes the economic efficiency of Uzbekistan's agrocluster system and develops recommendations for its further improvement. A comparison with the agrocluster models of the Netherlands, Turkey, and China has identified the competitive advantages and key development directions of Uzbekistan's agricultural clusters. The adoption of innovative technologies, strengthening of state support mechanisms, and expansion of export potential significantly enhance the efficiency of agroclusters. The Netherlands' smart agriculture technologies, Turkey's subsidy -based development model, and China's automated production systems have been identified as promising directions for Uzbekistan. The article provides recommendations on attracting investments, efficient resource utilization, and training of qualified specialists.
Keywords: agrocluster; agriculture; innovations; export; investments; efficiency; technological development